Invitation to world missions : a trinitarian missiology for the twenty-first century - Tennent, Timothy C. (Grand Rapids, MI : Kregel Publications, 2010)
This unique text is arranged in three parts according to the Trinity's roles, relationships, and activity. Tennent questions whether missions as currently conceptualized is adequate and he challenges the reader by building the book around key theological foundations such as "mission dei" and the "new creation" vision for the global church.--From publisher description.
Introduction -- Section A: Megatrends that are shaping twenty-first century missions -- From moratorium and malaise to 'selah' and rebirth -- Section B: The Triune God and the Missio dei -- A trinitarian, missional theology -- A trinitarian framework for missions -- God the Father : the providential source and goal of the Missio dei -- Section A: A missional perspective on the Bible -- The God of mission reveals his plan -- The sending Father and the sent church -- Section B: Creation, revelation, and the human response to God's rule -- A trinitarian, "new creation" theology of culture -- An evangelical theology of religions -- God the Son : the redemptive embodiment of the Missio dei -- Section A: Missions history as a reflection of the incarnation -- Turning points in the history of missions before 1792 -- The "great century" of missions, 1792-1910 -- The flowering of world Christianity, 1910-present -- Section B: Cross-cultural communication as a reflection of the incarnation -- The incarnation and the translatability of the Gospel -- Access and reproducibility in missions strategy -- Reflecting the incarnation in holistic missions -- God the Holy Spirit : the empowering presence of the Missio dei -- Section A: Empowering the church to embody the presence of the future -- The Holy Spirit, the book of Acts, and the Missio dei -- The church as the embodiment of the new creation -- Section B: Missionaries as agents of suffering and heralds of the new creation -- The suffering, advancing church -- Conclusion: the church as the reflection of the trinity in the world.
Includes bibliographical references and indexes.
Keywords: Missions -- Theory; Trinity